Magnetic anisotropy of 3nm diameter Co nanowires embedded in CeO2/SrTiO3(001): a ferromagnetic resonance study - Schio, P. (2014)
The magnetic anisotropy of 3-nm wide cobalt nanowires embedded in epitaxial CeO2/SrTiO3(001) layers is investigated by ferromagnetic resonance measurements. The measured magnetic shape and the magnetocrystalline anisotropies confirm that the Co nanowires have their main axes perpendicular to the film surface, and they are composed of hcp Co grains with the c-axes oriented along one of the <111> directions of the CeO2 matrix. The effects of such a peculiar structure on the magnetic anisotropy are addressed experimentally. The results show that the magnetic anisotropy of the wires is dominated by the magnetostatic term. The inhomogeneous structure of the wires leads to an effective magnetocrystalline anisotropy smaller than the bulk value of hcp Co.